Estudo da atividade antioxidante in vitro e caracterização cromatográfica em extratos de plantas medicinais da Amazônia - Silveira, Géssica Domingos da (2014)
Most of the free radicals generated in the body is derived from oxygen and are associated with the development of many diseases. Medicinal plants are a natural resource in the treatment prevention of diseases and have been used for the first healthcare. These properties of the plants are related to the presence of phenolic compounds which possess several pharmacological and antioxidant properties. The high performance liquid chromatography has been used to identify and quantify these compounds in plants. Therefore, this study developed and validated an HPLC - PAD method using gold as working electrode to characterize 12 phenolic compounds in herbal extracts from Amazon. The extracts from Connarus perrotettii var angustifolius, Mansoa alliacea, Cecropia palmata, Cecropia obtusa, Bauhinia variegata and Bauhinia alboflava showed the presence of at least one of the antioxidants compounds under study. Furthermore, the species showed in vitro antioxidant activity against reactive oxygen species. The acetate fraction of the species M. alliacea showed the highest in vitro antioxidant activity (70.85 ± 4.06%) against the superoxide radical. Front of the peroxyl radical, the species C. palmata was responsible for the hidhest antioxidant activity (95.33 ± 0.95%) and against hydroxyl radical species C. obtusa showed the highest scavenging activity (98.19 ± 5.93). The study of the in vitro antioxidant activity of these species coupled with chemical characterization of their extracts comprises an important key to potential in vivo studies. Moreover, the compounds identified and quantified in these species extracts have pharmacological properties and may be linked to popular use of these medicinal plants